Energy consumption, mechanical and metallographic properties of cryogenically treated tool steels - Savaş Ahmet Fevzi; Öktem Hasan; Öztürk Burak; Uygur İlyas; Küçük Özkan (Open Chemistry, 2023)
This article examines energy consumption, microstructure, mechanical properties, and the change in the wear amount during the machining of GGG-42 cast iron material with two types of guide cutting tool produced by powder metallurgy and casting method The tap. tool samples used as cutting tool material were first subjected to the traditional hardening process and then to two different cryogenic treatments (24–16 h) at −90°C. The internal structures of the guide samples obtained from conventional heat treatment and cryogenic treatment were examined with an optical microscope and Scanning Electron Microscope. The hardness changes were checked with Vickers measurement method. The wear amount forming after the threading process was measured with CLEMEX program in a light microscope. In addition, by measuring the current amount drawn during the machining of the cast iron with guide cutter tools, instantaneous power consumption during cutting and power consumption during chip removal were calculated. The application of heat treatment and cryogenic process increased the hardness of the guides. Moreover, the power consumption during the chip removal was also seen to increase. This can be commented that cutting tools produced with powder metallurgy perform better than the cutting tools produced via casting and 30% energy saving.